Metal-free hydroalkoxylation of ynesulfonamides with alcohols. Issue 16 (5th April 2022) - Wang, Hanhan; Hu, Mengjun; Wang, Xiao-Na; Chang, Junbiao
Abstract : A facile and efficient TfOH-catalyzed hydroalkoxylation of ynesulfonamides with diverse alcohols is described for the preparation of alkoxy-substituted enamides in high yields with excellent stereoselectivity and wide functional group tolerance. Abstract : Efforts for developing a convenient and expeditious method for synthesizing alkoxy-substituted enamides via nucleophilic addition of alcohols to ynesulfonamides are described. This sequence is completely regioselective and highly stereoselective, and leads to the hydroalkoxylation products in high yields under mild reaction conditions.